The role of physical activity in various forms of practice of amateur and professional chess players - Vasilenko, I.V.; Tkachenko, O.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the dependence of physical activity in various forms on chess practice at the professional and amateur levels. Methods and structure of the study. To study the influence of chess practice on the physical activity of young people, a qualitative sociological study was conducted using the in-depth interview method, in which 20 people aged 18 to 35 participated. The interview guide was compiled according to the following research questions: the significance of chess in the informant’s life, the main types of physical activity of chess players, preferred sports, the significance of physical education for chess as a sport, as a hobby and leisure activity. The interpretation of results was carried out using the method of progressive approximation and illustration. Results and conclusions. It was established that amateur chess players do not associate their physical activity with their interest in chess; on the contrary, professionals and semi-professionals approach physical activity with particular attention, which has a positive effect not only on their general health but also allows them to properly recover after intellectual work, as well as to train qualities significant for chess sport: concentration, endurance, stress resistance. The significance of combining physical and intellectual development is explicated in the emergence of hybrid sports, such as, for example, chess boxing, which combines a game of chess and a boxing bout.